From the Iowa Birdline, September 1-November 30, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Summary of the Iowa Birdline update for September 1-November 30, 1991. Highlights of the update were September sightings of a Western Wood Pewee and a Red Phalarope, as well as October sightings of a Groove-billed Ani, a Common Ground Dove, and adult and juvenile Sabine's Gulls. Also of note was the outstanding variety of rarities found at Pleasant Creek State Park in November. Epson - sheet feed